Measurements of electron energy distribution on electron cyclotron resonance plasma operated with hydrogen gas - Mishra, L.N.; Fredriksen, Å. (Journal of Nepal Physical Society, 2021)
This article deals with the production of electron cyclotron resonance hydrogen plasma in a closed gas chamber called Menja device. For this purpose, 2.45 GHz frequency and various power i.e. 0 - 500 W are employed. The flow of hydrogen gas is controlled manually with the range 1.5 – 10 sccm maintaining pressure range 10-5 – 10-4 mbar. The Langmuir probe technique is used to drag the electrons and ions by biasing the probe positively and negatively to study the key parameters such as ion saturation current, floating potential, plasma potential, electron temperature and plasma density. Besides these, to obtain information on electron energies and their interaction with plasma, the electron energy distribution function (EEDF) has been studied with the help of 2nd derivative of current obtained from the differentiator. For this purpose, an analogue differentiation circuit was built and tested.